Active Learning Method In 2013 Curriculum Based PAI Learning And Its Impact On Student - Muchtarom, Muchtarom (The International Journal of Education Management and Sociology, 2024)
This research was conducted to analyze the influence of active learning on PAI learning based on the 2013 Curriculum and its impact on students. This research method uses a descriptive qualitative approach. The data sources in this research are primary data and secondary data. Primary data was obtained from direct interviews with the Principal, Deputy Principal for Curriculum, Deputy Principal for Facilities, Student Affairs, PAI lesson teachers, and students. Observations at the research location. Meanwhile, secondary data sources were obtained from the study of documents, manuscripts, and archives related to the implementation of active learning in PAI based on the 2013 Curriculum and its impact on students at SMA Muhammadiyah 1 Bandung. The conclusion according to the results of the analysis is that the active learning method in PAI learning is based on the 2013 Curriculum, which is expressed through religious activities in PAI learning both in the classroom and outside the classroom. Meanwhile, the 2013 Curriculum active learning activities in PAI learning were successful and had an impact on forming students' religious character. This is proven by the small number of students who violate the active learning methods implemented